Paths and pathways that generate cell-type heterogeneity and developmental progression in hematopoiesis - Girard, Juliet R; Goins, Lauren M; Vuu, Dung M; Sharpley, Mark S; Spratford, Carrie M; Mantri, Shreya R; Banerjee, Utpal (eLife, 2021)
Mechanistic studies of Drosophila lymph gland hematopoiesis are limited by the availability of cell-type-specific markers. Using a combination of bulk RNA-Seq of FACS-sorted cells, single-cell RNA-Seq, and genetic dissection, we identify new blood cell subpopulations along a developmental trajectory with multiple paths to mature cell types. This provides functional insights into key developmental processes and signaling pathways. We highlight metabolism as a driver of development, show that graded Pointed expression allows distinct roles in successive developmental steps, and that mature crystal cells specifically express an alternate isoform of Hypoxia-inducible factor (Hif/Sima). Mechanistically, the Musashi-regulated protein Numb facilitates Sima-dependent non-canonical, and inhibits canonical, Notch signaling. Broadly, we find that prior to making a fate choice, a progenitor selects between alternative, biologically relevant, transitory states allowing smooth transitions reflective of combinatorial expressions rather than stepwise binary decisions. Increasingly, this view is gaining support in mammalian hematopoiesis.
Keywords: hematopoiesis; crystal cells; lymph gland; blood progenitors; stem cells; intermediate progenitors